Compact UWB Band-Notched Antenna with Integrated Bluetooth for Personal Wireless Communication and UWB Applications - MuhibUr Rahman (18174361) (2019)
A compact band-notched UWB (Ultra-Wide Band) antenna with integrated Bluetooth is developed for personal wireless communication and UWB applications. The antenna operates at the UWB frequency band (3.1–10.6 GHz) as well as Bluetooth (2.4–2.484 GHz), with band-notch characteristics at the Wireless Local Area Network (WLAN) frequency band (5–6 GHz). A new technique of integrating Bluetooth within a UWB band-notched antenna is developed and analyzed. The UWB frequency band is realized by utilizing a conventional cylindrical radiating patch and a modified partial ground plane. The Bluetooth band is integrated using a miniaturized resonator with the addition of capacitors. Further, to mitigate the interference of the WLAN frequency band within the UWB spectrum, a conventional slot resonator is integrated within the radiator to achieve the task. The antenna is designed and fabricated, and its response in each case is provided. Moreover, the antenna exhibits a good radiation pattern with a stable gain in the passband. The present antenna is also compared to state-of-the-art structures proposed in the literature. The miniaturized dimensions (30 × 31 mm2) of the antenna make it an excellent candidate for UWB and personal wireless communication applications. Other Information Published in: Electronics License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/electronics8020158